Competition law and the Malaysian financial services market: an analysis of the structure and level of competition in the market - Abdul Rahman, Nasarudin; Mohamad Faudzi, Mohd Hasbullah; Ahamat, Haniff; Abd Ghadas, Zuhairah Ariff (Inderscience Publishers, 2016)
Competition law seeks to protect the process of competition on the market by preventing anti-competitive behavior such as abuse of dominant position and mergers that have the effect of lessening competition in the market. One of the important considerations in the competition law anaylsis is the assessment of market structure and the level of competition in which firms compete with each other. This paper attempts to analyze structure of the market and the level of competition in the Malaysian financial market by adopting two measures, namely, concentration ratio (CR) and Herfindahl-Hirschman Index (HHI). The study shows that the banking sector can be considered as ‘unconcentrated’. However, based on ownership (foreign or local) the study indicates such sector is ‘moderately’ concentrated. For the insurance sector, general insurance can be considered as ‘unconcentrated’ whereas life insurance is ‘highly concentrated.’ Even though the findings from the market concentration study are not by itself an evidence of anti-competitive behavior, they assist the competition regulator to understand the structure and the nature of the Malaysian financial services market which may facilitate anti-competitive conduct or provide strong incentive for market players to engage in anti-competitive conduct such as collusion and abuse of market power.